2011
DOI: 10.1177/2158244011430988
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Corporations and Corporate Social Responsibility

Abstract: Comparative studies have demonstrated that the themes for corporate social responsibility (CSR) initiatives are different among nations and geographic regions based on their cultural, political, legal, social, and economic contexts. In this research, which was conducted on 56 corporations from IMI100 (100 Iranian companies with highest annual sales, ranked by Industrial Management Institute or IMI), CSR themes in priority have been identified. Data collected from a semistructured questionnaire and some complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The literature generally acknowledges the challenges of conducting this kind of study in such large corporations (Wolff, 2004). In particular, in the Iranian context, the challenges seem more fundamental due to factors such as the highly bureaucratic setting of corporations, the general reluctance of people to share information with others, and little attention to research activities (Chapardar & Khanlari, 2011). In addition, because of the CFOs' responsibilities as well as the sensitive topics covered by the survey, a small rate of response was a priori expected.…”
Section: Methodsmentioning
confidence: 99%
“…The literature generally acknowledges the challenges of conducting this kind of study in such large corporations (Wolff, 2004). In particular, in the Iranian context, the challenges seem more fundamental due to factors such as the highly bureaucratic setting of corporations, the general reluctance of people to share information with others, and little attention to research activities (Chapardar & Khanlari, 2011). In addition, because of the CFOs' responsibilities as well as the sensitive topics covered by the survey, a small rate of response was a priori expected.…”
Section: Methodsmentioning
confidence: 99%
“…This was partially due to the ongoing US-led economic sanctions on Iran which primarily targeted the country's energy sector. The farreaching implications of the most recent US-led sanctions on the country's currency and auto industry (Felsenthal et al 2013) are twofold: a pressing need for the government to seek new sources of revenue for the government expenditure, and limits to the extent to which managerial actions of foreign affiliates in Iran's auto industry bring about a marked transformation of business-governmentsociety relations (see Chapardar and Khanlari 2011).…”
Section: Discussionmentioning
confidence: 99%
“…****************** Place Table 1 around here ****************** A review of the previous literature shows that the dominant existing empirical studies employed sample data based on developed countries such as the EU or US [37], and the results show a positive impact of CSR on firm performance. Despite the lack of studies focusing on developing and underdeveloped countries, especially the context of Pakistan and Thailand, and being underutilized as a selected sample in worldwide research [87], it is also expected that similar outcomes will be found in Pakistan and Thailand.…”
Section: Samplementioning
confidence: 99%